2021
DOI: 10.1302/2633-1462.27.bjo-2021-0062.r1
|View full text |Cite
|
Sign up to set email alerts
|

Should isolated morbid obesity influence the decision to operate in hip and knee arthroplasty?

Abstract: Aims We studied the outcomes of hip and knee arthroplasties in a high-volume arthroplasty centre to determine if patients with morbid obesity (BMI ≥ 40 kg/m2) had unacceptably worse outcomes as compared to those with BMI < 40 kg/m2. Methods In a two-year period, 4,711 patients had either total hip arthroplasty (THA; n = 2,370), total knee arthroplasty (TKA; n = 2,109), or unicompartmental knee arthroplasty (UKA; n = 232). Of these patients, 392 (8.3%) had morbid obesity. We compared duration of operation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Previous research on the implications of obesity on THA has been conducted using traditional and contemporary THA approaches, including the direct anterior (DA) approach and posterior approach. [10][11][12] The anteriorbased muscle-sparing (ABMS) approach is a lesserknown comprehensive approach that was described by Rottinger et al in 2004, 13 using the interval between the tensor fasciae latae (TFL) posteriorly and the gluteus medius (GM) muscle anteriorly. [13][14][15] This approach is a safe and effective approach that is muscle-sparing and can be performed in the supine or lateral position.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on the implications of obesity on THA has been conducted using traditional and contemporary THA approaches, including the direct anterior (DA) approach and posterior approach. [10][11][12] The anteriorbased muscle-sparing (ABMS) approach is a lesserknown comprehensive approach that was described by Rottinger et al in 2004, 13 using the interval between the tensor fasciae latae (TFL) posteriorly and the gluteus medius (GM) muscle anteriorly. [13][14][15] This approach is a safe and effective approach that is muscle-sparing and can be performed in the supine or lateral position.…”
Section: Introductionmentioning
confidence: 99%
“… 4 - 6 Morbid obesity is associated with a poorer prognosis and an increased risk of infection in hip and knee arthroplasty (joint arthroplasty surgery). 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies [13][14][15][16][17] have expressed the opposite view that there is no association between BMI and the occurrence of VTE events after TKA and the increased risk of prosthesis revision. Crookes et al [16] showed that there was no significant difference in VTE events between patients with morbidly obese (BMI ≥40 kg/m 2 ) and patients with BMI < 40 kg/m 2 . Tang et al [17] divided the patients into 5 groups according to BMI and found that there was no statistical difference in the incidence of total VTE among different BMI groups.…”
Section: Introductionmentioning
confidence: 99%